2014
DOI: 10.1007/s12665-014-3451-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rainfall variation and landscape change on runoff and sediment yield from a loess hilly catchment in China

Abstract: The semiarid Chinese Loess Plateau is notorious for severe drought, water erosion, and environmental degradation. Changes in landscape patterns and rainfall are key drivers that determine the dynamics of runoff loss and sediment yield from catchments. These factors have crucial implications for management of other fragile ecosystems around the globe. In this study, responses of surface runoff and sediment yield to land use and rainfall in a typical loess hilly catchment in 1997, 2005, and 2010 were analyzed. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…Based on data collected from hydrological station, Zhao et al (2014) reported a continuous decline for the runoff depth in the Yanhe Basin since 1997, and the average value of annual runoff depth was 24.76 mm between 1997 and 2010 . The decline trend of water yield in the study period was also confirmed in the Loess Plateau (Wei et al, 2015).…”
Section: Changes In Annual Water Yield (Wy) Over Yanhe Basinsupporting
confidence: 62%
“…Based on data collected from hydrological station, Zhao et al (2014) reported a continuous decline for the runoff depth in the Yanhe Basin since 1997, and the average value of annual runoff depth was 24.76 mm between 1997 and 2010 . The decline trend of water yield in the study period was also confirmed in the Loess Plateau (Wei et al, 2015).…”
Section: Changes In Annual Water Yield (Wy) Over Yanhe Basinsupporting
confidence: 62%
“…The mean annual pan evaporation reaches 1515 mm. The soil type belongs to calcic Cambisol (FAO, 1990), developed from loess material, with the average soil depth varying from 40 to 60 m (Chen et al, 2010;Wei et al, 2015). In this area, deep percolation can be neglected and groundwater is unavailable for vegetation growth and restoration (Yang et al, 2012).…”
Section: Site Descriptionmentioning
confidence: 99%
“…However, various studies have reported that a reduction in river runoff occurred as an outcome of the enhanced soil conservation in the Loess Plateau (Li et al, 2009;Gao et al, 2015;Wei et al, 2015;Liang et al, 2015). River runoff from the Loess Plateau contributes to the tributaries of the Yellow River; therefore, a reduction in runoff from the plateau will not only influence the provisioning of water for local residents, but will also affect the downstream flow in the Yellow River (Tang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%